METHODOLOGICAL POTENTIAL OF PROSOPOGRAPHY IN MODERN HISTORICAL SCIENCE: ON YU. Y. YUMASHEVA’S MONOGRAPH "ESSAYS ON PROSOPOGRAPHY: HISTORY. THEORY. RESEARCH" (Journal of history, 2026)
This review examines the monograph by Y. Yumasheva, Essays on Prosopography: History. Theory. Research : Monograph / Yu. Yu. Yumasheva. – Moscow: Direct-Media, 2026. – 456 p.: ill., devoted to the theoretical and methodological problems of prosopography. The structure of the work, its conceptual foundations, and scholarly significance are analyzed. Particular attention is paid to the historical, theoretical, and historiographical aspects of the study, as well as to the role of the essay genre in organizing the material. The strengths of the work are identified, including its interdisciplinary nature and methodological novelty. The review concludes that the monograph makes a significant contribution to the development of contemporary historical scholarship.
Keywords: prosopography, methodology of history, historical science, digital humanities, historiography, collective biographies, scientific methods.